PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PRODUCTION DEPARTMENT DI PT. MNC GS HOMESHOPPING - Brenda Carmanita Aurellia; Heribertus Jani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of workload and work environment on the performance of employees of the production department at PT. MNC GS Homeshopping. The research method used is quantitative with random sampling method and using SPSS 26 program by collecting data through questionnaires distributed using google form. The number of samples used in the following survey is 78 respondents from 80 employees of the production department with a total population of 300 employees of PT. MNC GS Homeshopping. The results obtained that the workload has a positive and significant effect on employee performance on the contrary, the work environment has a negative and insignificant effect on employee performance. The findings of this study can be used as a reference for PT. MNC GS Homeshopping to distribute the workload evenly.